The Influence Of Financial Digitalization On The Operational Efficiency Of Culinary Sector Msmes With Financial Literacy As A Mediating Variable - Meidy , Rozie; Khasanah , Siti Fatimatul (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to examine the influence of financial digitalization on the operational efficiency of culinary sector MSMEs with financial literacy as a mediating variable. Several key issues addressed in this research include limited access to relevant training programs, low levels of financial understanding or literacy, limited financial resources, and inadequate technological infrastructure. The sample in this study consists of 82 culinary MSMEs located in Musi Rawas Regency. Data collection was conducted using questionnaires, and the analytical method employed is Structural Equation Modeling (SEM) using Smart PLS 3.0 software. The results of the study indicate that the first hypothesi financial digitalization affects the operational efficiency of MSMEs is supported. The second hypothesis financial digitalization affects financial literacy is also supported. Furthermore, the third hypothesis financial digitalization through financial literacy affects the operational efficiency of MSMEs is accepted.